An Efficient Security System for CABAC Bin-Strings of H.264/SVC - Asghar, M. N.; Ghanbari, M. (IEEE transactions on circuits and systems for video technology, 2013)
The distribution of copyrighted scalable video content to differing digital devices requires protection during rendering and transmission. In this paper, we propose a complete security system for H.264/scalable video coding (SVC) video codec and present a solution for the bit-rate and format compliance problems by careful selection of entropy coder syntax elements (bin-strings) for selective encryption (SE), and the problem of managing multiple layer encryption keys for scalable video distribution. A standard key management protocol, multimedia Internet keying protocol, is implemented for the hierarchical key generation mechanism, in which a subscriber has only one encryption key to unlock all scalable layers that have been subscribed to. The evaluation demonstrates the resulting video quality degradation arising from SE for many CIF and 4 CIF test video sequences, without there being any impact upon the bit-rate or format compliancy, and with small computational delay. The security and statistical analysis performed further verify the effectiveness of the proposed security system for H.264/SVC. The proposed system is highly suitable for video distribution to users who have subscribed to a varying degree of video quality on devices with medium to high computational resources.